The Ottoman Safadi conflict and the occupation of Basra 1546-1775 - Taher Hawaz, Assist. Lect . Sanaa (Basra studies journal, 2025)
has This research deals with the Ottoman Safavid conflict over Iraq in general and the attempts to occupy Basra in particular in the period(1546-1775), it explains the most important campaigns launched on Iraq and Basra, and indicating the reasons that led to the two countries' quest for occupation and control, which led Iraq to be a field for their expansionist military operations. The conflict between the two countries has continued throughout history despite the conclusion of many treaties, but this dispute did not lose any of their territories, and the only loser was the disputed territory, as Iraq became an easy morsel for both parties. Basra in particular was of great importance to the two countries, as both sought to occupy and control it several times, due to the importance of its geographical location, as it is the main port of Iraq on the Shatt al-Arab, as well as its economic importance for Iranian cities located on the border between Iraq and Iran, and thus occupied a prestigious commercial center whose importance increased in the early seventeenth century.